2022
DOI: 10.3389/fvets.2022.1017954
|View full text |Cite
|
Sign up to set email alerts
|

Companion animal adoption and relinquishment during the COVID-19 pandemic: Peri-pandemic pets at greatest risk of relinquishment

Abstract: The COVID-19 pandemic has created a situation globally where companion animals may be at increased risk of relinquishment and abandonment due to multiple interrelated factors. The aims of this study were to establish the prevalence of self-reported adoption and relinquishment of cats and dogs during the pandemic, and to identify characteristics associated with relinquishment. A survey was distributed to 4,000 participants across several countries including the UK, USA, Canada, Italy, Spain and France. N = 3,94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Furthermore, the increase in first time pet-ownership around the time of the COVID-19 pandemic makes education of pet owners of particular importance moving forward (Murphy et al 2022 ). For example, Carroll et al ( 2022 ) found that 63.2% of people that had relinquished a cat or dog were first-time pet owners, suggesting that lack of experience and knowledge may contribute to undesirable outcomes for companion animals. However, owners may possess knowledge of best practice, yet they may not exhibit corresponding behaviour based on this knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the increase in first time pet-ownership around the time of the COVID-19 pandemic makes education of pet owners of particular importance moving forward (Murphy et al 2022 ). For example, Carroll et al ( 2022 ) found that 63.2% of people that had relinquished a cat or dog were first-time pet owners, suggesting that lack of experience and knowledge may contribute to undesirable outcomes for companion animals. However, owners may possess knowledge of best practice, yet they may not exhibit corresponding behaviour based on this knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a lack of research into animal rescue staff and volunteer experiences during COVID-19 (Powell et al 2021 ), with most studies focusing on the companion animal owners (e.g. Packer et al 2021 ; Siettou 2021 ; Carroll et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of cats and dogs being acquired online continues to rise. For example, Carroll et al ( 2022 ) found that, of 3,945 current or previous dog and cat owners sampled in 2020, 39.0 and 26.6%, respectively, acquired their pet online. From data collected in early 2022, the 2022 PAWS report found that 63% of dogs and 43% of cats were acquired from an online source (People’s Dispensary for Sick Animals [PDSA] 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there could be increased time to care for a companion animal. As adoption availability increases [ 4 ], people who want to adopt but cannot do it due to availability could be more likely to do so after the crisis [ 14 ].…”
Section: Introductionmentioning
confidence: 99%